Estudio retrospectivo de cien cánceres gástricos operados en el Hospital de Clínicas entre los años 1969 y 1989 - Pereyra, Jorge; Varela, Daniel; Fernández, Ricardo (Cirugía del Uruguay, 1991)
A series of 100 gstric cancers operated in the Surgical Clinics at the Hospital de Clínicas between 1969 and 1989 is analysed lmportant limitations in diagnosis, parac/inical study, and treatment are identified These are the bases for orientation as to where to direct efforts in order to improve study and treatment of this pathology.